2019
DOI: 10.1016/j.seizure.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice towards epilepsy among medical staff in Southern China: Does the level of hospitals make a difference?

Abstract: To assess knowledge, attitudes, and practice (KAP) toward epilepsy among medical staff from different levels of hospitals in Southern China. Method: An adapted and structured questionnaire was administered to medical personnel from tertiary (n = 451) and basic-level (n = 448) hospitals in Southern China. The questionnaire comprised of three domains which consisted of 6 items for awareness, 12 items for knowledge and a 14 item scale for attitudes. Results: Almost 40% of medical staff in basic-level hospitals he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Some demographic characteristics have been found to be related with health workers' knowledge and attitudes toward a certain disease, including age, title, education level, and hospital levels ( 14 16 ). Yang et al indicated the knowledge and response to seizures among medical staff in tertiary hospitals were better than those of basic-level hospitals ( 18 ). Interestingly, we found the level of hospitals may also affect their health workers' understanding of COVID-19 during the epidemic outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some demographic characteristics have been found to be related with health workers' knowledge and attitudes toward a certain disease, including age, title, education level, and hospital levels ( 14 16 ). Yang et al indicated the knowledge and response to seizures among medical staff in tertiary hospitals were better than those of basic-level hospitals ( 18 ). Interestingly, we found the level of hospitals may also affect their health workers' understanding of COVID-19 during the epidemic outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Medical staff were classified into two groups according to the level of hospitals they worked in based on the Hospital Classification Standards in China. General hospitals in China are categorized into three levels: the first-level hospitals should provide the basic medical care, prevention, rehabilitation, and health care services in small or medium-sized towns ( 18 ), the second-level hospital hospitals have to provide diagnosis and treatment of common and frequently occurring diseases, receiving referral patients from primary medical institutions and tertiary hospitals and undertaking teaching, training and scientific research tasks ( 18 , 19 ), and the third-level hospitals are responsible for providing the maximum range of medical knowledge and technical infrastructure in diagnostics and treatment of almost all diseases ( 18 , 20 ). In this study, the first-level and second-level hospitals were considered as basic-level hospitals and the third-level hospitals were considered as tertiary hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As children develop physically and psychologically, sick children often develop psychobehavioral abnormalities, such as attention-deficit/hyperactivity disorder, autism, and mood disorders that affect the child's education, future work, and marital status ( 5 ). In addition to comprehensive care for the child, caregivers of children with epilepsy also need to deal with developmental problems, educational and marital problems, and the stigma caused by the disease ( 6 ). It has been shown that most parents of children with epilepsy have negative perceptions of others' reactions (53.3%).…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason for this difference is that children with epilepsy affect caregivers' mental adaptation beyond the effects of family resilience and social support alone. For example, due to social misconceptions and negative attitudes, epilepsy is regarded as a kind of mental illness in China, the families often experience severe stigma, especially in rural areas (42). This is considered as the greatest handicap for people with epilepsy rather than the disability caused by recurrent seizures, causing families tremendous psychological burden (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%